2016
DOI: 10.1111/acps.12684
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma and mixed episodes are associated with poor response to lithium in bipolar disorders

Abstract: Objectives: Reliable predictors of response to lithium are still lacking in bipolar disorders (BD).However, childhood trauma has been hypothesized to be associated with poor response to lithium. Methods:We included 148 patients with BD, euthymic when retrospectively and clinically assessed for response to lithium and childhood trauma using reliable scales.Results: According to the "Alda scale", the sample consisted in 20.3% of excellent responders, 49.3% of partial responders and 30.4% of non-responders to lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
41
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 55 publications
10
41
0
2
Order By: Relevance
“…Insulin resistance was found to be associated with poor response to lithium in one study, in keeping with the studies showing an association with BMI . While we did not consider childhood trauma as a ‘clinical’ predictor of treatment response, one included study examined this among other features . This study suggested physical abuse was an independent predictor of poor lithium response after accounting for many clinical characteristics.…”
Section: Resultssupporting
confidence: 71%
“…Insulin resistance was found to be associated with poor response to lithium in one study, in keeping with the studies showing an association with BMI . While we did not consider childhood trauma as a ‘clinical’ predictor of treatment response, one included study examined this among other features . This study suggested physical abuse was an independent predictor of poor lithium response after accounting for many clinical characteristics.…”
Section: Resultssupporting
confidence: 71%
“…Childhood maltreatment might lead to greater instability through a resistance to mood stabilizers, especially when a lower response to lithium has been reported to be associated with childhood maltreatment . 22 Childhood maltreatment might also lead to a greater risk of rapid cycling, through more depressive episodes (mediation effect), that are more likely to be then treated with antidepressants which are a classical risk factor for rapid cycling in BD. 34 For those cases with high genetic risk, the association between childhood maltreatment and a more unstable clinical profile (greater risk for rapid cycling) is lost.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical variables were collected during the clinical assessment and selected a priori: age at onset, number of episodes (based on manic and depressive episodes), lifetime presence of mixed episode, of psychotic features during mood episodes, of rapid cycling, of substance abuse disorder and of suicide attempt. These clinical variables were selected for the following reasons: (a) they are indicators of the complexity and/or severity of the clinical expression of BD; and (b) they have been associated with childhood trauma in two previous study from our groups and a recent meta‐analysis …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Childhood maltreatment also markedly increases the severity of the expression of BD, leading to earlier, more suicidal and recurrent forms of the disorder 22 , and lower response to conventional mood stabilizers. 23 Childhood maltreatment also interacts with cannabis use during adolescence to increase the severity of the clinical expression of BD. 24,25 Childhood trauma might lead to BD by modifying amygdala volume and prefrontolimbic functional connectivity.…”
mentioning
confidence: 99%